Why dairy farms are exiting the industry - Armknecht, Cassandra (Kansas State University, 2024)
Dairies in the last twenty years have increased from eighty-five cows to 337-cows in 2022 (O’Leary 2023). Cow numbers are over nine million with more cows on fewer dairy farms. Production per cow has increased in the past twenty years by 138 pounds to an average of 24,067 pounds. The nine million dairy cows used to be on over 500,000 farms and now are on 27,932 dairies. The increase of production per cow has contributed to the oversupply of milk on the market. Aggregate cow numbers have remained the same for over the past ten years. There are multiple reasons why dairy farmers sell out. Number one is financial reasons and there are historical reports to back up this claim. There were only two profitable years in the last twenty years according to the Farm Bureau analysts report (Nepveux 2021). The variable costs of dairy farming make it very volatile, thus a high-risk business model. Transportation has become expensive in the last twenty years as dairy farmers pay for hauling, added stop fees, and a newly added fuel surcharge. The changing American diet to plant-based foods may also add to the decline in demand for dairy products. A survey was conducted to look at reasons dairy farmers have quit milking. A survey with eighteen questions tailored for why dairy farmers have quit was conducted with the questions ranging from what state your dairy is located, to acres farmed, labor, adverse financial, family transition, divorce, disease, management practices, profitability, retirement, and milk price. One hundred seventeen responses were obtained from the survey. The farm sizes ranged from forty cows to 2,700 and owning no land to owning 5,000 acres. There are many factors that contribute to why a farmer sold the dairy but the main reason to sell the dairy cows were financial reasons.
Keywords: Dairy farms; Selling out; Dairies; Dairy cows